Nanomedicines for the treatment of genitourinary neoplasms - Shaowen Wang; Yongzhi Li; Xiaoting Sun; Tianping Song; You Wang; Ziyue Xue; Yang Guo; Jiawei Wang; Zhijia Cui; Peijian Lu; Haifeng Huang; Diqing Pan; et al. (Materials Today Bio)
Genitourinary neoplasms, accounting for 20–25 % of all malignant tumors, are associated with high mortality rates and pose significant challenges to clinical treatment. Especially for young patients who have reproductive demands, pharmacotherapy is a promising non-surgical strategy to improve the survival rate and quality of life. However, the distinctive interface between physiological milieu complicates effective drug delivery. Nanomedicines offer distinct advantages, including mitigating clearance, enabling precise tumor targeting, and intracellular drug delivery. Unlike most reviews about the area, which focused on a specified tumor or nanomedicine, this review, for the first time, systematically summarized the application of extensively investigated nanomedicines in the entire genitourinary neoplasms, and provided the latest and most comprehensive insights. Furthermore, we proposed the shortage of therapeutic activity and challenges in nano-therapy, and highlighted the potential of innovative and functional nanomedicines as well as emerging technology.